Factors influencing the work passion of Chinese community health service workers: an investigation in five provinces - Luo, Zhenni (BioMed Central, 2014)
BACKGROUND: After the implementation of new healthcare reform, Chinese government paid increasing attention to developing community health service (CHS). The current focus is mainly on cultivating community general practitioners but paying less attention to the working status and occupational demands of in-service CHS workers. Work passion is playing an important role for medical workers. With work passion, CHS workers’ team will become more stable and more effective, ensuring the sustainable development of CHS system. At present, the work passion of CHS workers is relatively low. Studying on influencing factors of work passion of CHS workers, promoting their work passion, and making them keep enthusiasm for work are significant. METHODS: A total of 100 CHS organizations were sampled randomly in 10 cities from 5 Chinese provinces for this study. A total of 3450 CHS workers from these CHS institutions took part in the surveys. Questionnaires were used to collect data, including socio-demographic information, work passion and opinion on influencing causes, and work-related satisfaction. Pearson chi-square statistical method was used to identify the factors related to CHS workers’ work passion. Binary logistic regression was performed to determine the significant factors that influence CHS workers’ work passion. RESULTS: A total of 38.77% of those who accomplished the questionnaire expressed that they didn’t have passion for current work. The related factors that influence CHS workers’ work passion are (1) socio-demographic factors such as age, and years of employment, and (2) other work-related factors such as learning and training opportunities, compensation packages, work stress, and personal development opportunities. CHS workers were most dissatisfied with the balance between remuneration and workload, job promotion opportunities. CONCLUSIONS: Based on the results, the government should concern for CHS workers’ working status and work-related demands, pay more attention and meet their demands for reasonable compensation packages and self-development, balance the income and workload, provide more learning and training opportunities and personal development opportunities for CHS workers, in order to promote CHS workers’ work satisfaction, improve their work passion and enthusiasm.